The Prevalence of Cannabinoid Hyperemesis Syndrome Among Regular Marijuana Smokers in an Urban Public Hospital. Issue 6 (23rd February 2018) - Habboushe, Joseph; Rubin, Ada; Liu, Haoming; Hoffman, Robert S.
Abstract: Epidemiological data, including prevalence, for cannabinoid hyperemesis syndrome (CHS) remain largely unknown. Without these data, clinicians often describe CHS as 'rare' or 'very rare' without supporting evidence. We seek to estimate the prevalence of CHS in a population of patients presenting to a socio‐economically and racially diverse urban Emergency Department of a public hospital. This study consisted of a questionnaire administered to a convenience sample of patients presenting to the ED of the oldest public hospital in the United States. Trained Research Associates (RAs) administered the questionnaire to patients between the ages of 18–49 years who reported smoking marijuana at least 20 days per month. The survey included questions related to CHS symptoms (nausea and vomiting) and Likert scale rankings on eleven symptom relief methods, including 'hot showers'. Patients were classified as experiencing a phenomenon consistent with CHS if they reported smoking marijuana at least 20 days per month and also rated 'hot showers' as five or more on the ten‐point symptom relief method Likert scale for nausea and vomiting. Among 2127 patients approached for participation, 155 met inclusion criteria as smoking 20 or more days per month. Among those surveyed, 32.9% (95% CI, 25.5–40.3%) met our criteria for having experienced CHS. If this is extractable to the general population, approximately 2.75 million (2.13–3.38 million) Americans may suffer annually from a phenomenon similar to CHS.